Psychological Science Is Not Race Neutral - Dupree, Cydney H.; Kraus, Michael W. (Perspectives on psychological science, 2022)
In their analysis in a previous issue of Perspectives on Psychological Science, Roberts and colleagues argued that the editors, authors, and participants throughout subfields of psychological science are overwhelmingly White. In this commentary, we consider some of the drivers and consequences of this racial inequality. Drawing on race scholarship from within and outside the field, we highlight three phenomena that create and maintain racial inequality in psychology: (a) racial ignorance, (b) threats to belonging, and (c) racial-progress narratives. We close by exploring steps that journals and authors can take to reduce racial inequality in our field, ending with an appeal to consider the experience of scholars of color in race scholarship and in psychological science more broadly.